Ответ:
Пошаговое объяснение:
1) y=(8x-5)^17.
y'=((8x-5)^17)' = 17(8x-5)^16 * (8*x'-5') = 17*8(8x-5)^16 = 136(8x-5)^16.
2) y=cos(x^4-15).
y' = (cos(x^4-15))' = -sin(x^4-15)*(x^4)'-15'} = -sin(x^4-15)(4x^3-0) =
= -4x^3sin(x^4-15).
********************
1) y=(x^3+6x)^12 при x=0.
y'=((x^3+6x)^12)' = 12(x^3+6x)^11 * (x^3+6x)' = 12(x^3+6x)^11 *(3x^2+6*1)=
=12(x^3+6x)^11 *(3x^2+6). =>
при x=0 => y'= 12(0^3+6*0)^11*(3*0^2+6) = 12*0*(6) = 0.
2) y=√(4x²-3) при x=1.
y'=(4x²-3)^(1/2) = 1/2(1/√4x²-3) * (4x²-3)' = 1/2(1/√4x²-3) * (4*2*x-0) =
=4x/(√(4x²-3)).
при x=1 => y'=4*1/(√4*1²-3) = 4/1=4.
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
1) y=(8x-5)^17.
y'=((8x-5)^17)' = 17(8x-5)^16 * (8*x'-5') = 17*8(8x-5)^16 = 136(8x-5)^16.
2) y=cos(x^4-15).
y' = (cos(x^4-15))' = -sin(x^4-15)*(x^4)'-15'} = -sin(x^4-15)(4x^3-0) =
= -4x^3sin(x^4-15).
********************
1) y=(x^3+6x)^12 при x=0.
y'=((x^3+6x)^12)' = 12(x^3+6x)^11 * (x^3+6x)' = 12(x^3+6x)^11 *(3x^2+6*1)=
=12(x^3+6x)^11 *(3x^2+6). =>
при x=0 => y'= 12(0^3+6*0)^11*(3*0^2+6) = 12*0*(6) = 0.
2) y=√(4x²-3) при x=1.
y'=(4x²-3)^(1/2) = 1/2(1/√4x²-3) * (4x²-3)' = 1/2(1/√4x²-3) * (4*2*x-0) =
=4x/(√(4x²-3)).
при x=1 => y'=4*1/(√4*1²-3) = 4/1=4.